Sacral Myeloid Sarcoma Manifesting as Radiculopathy in a Pediatric Patient: An Unusual Form of Myeloid Leukemia Relapse - Joana Ruivo Rodrigues; Manuel João Brito; Rui Pedro Faria Pais; Sílvia Carvalho (Case Reports in Radiology)
Myeloid sarcoma (MS), granulocytic sarcoma or chloroma, is defined as a localized extramedullary mass of blasts of granulocytic lineage with or without maturation, occurring outside the bone marrow. MS can be diagnosed concurrently with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS). The authors report a case of sacral MS occurring as a relapse of myeloid leukemia in a 5-year-old girl who was taken to the emergency department with radiculopathy symptoms.